Etiology and factors associated with urogenital fistula among women who have undergone cesarean section: a cross-sectional study - Raha Maroyi; Madeline K. Moureau; Heidi W. Brown; Rane Ajay; Gloire Byabene; Denis M. Mukwege (BMC, 2023)
Abstract Background The prevalence and impact of fistulas are more common in developing countries with limited access to emergency obstetric care. As a result, women in these settings often experience adverse psychosocial factors. The purpose of this study was to describe the characteristics of Congolese women who developed urogenital fistula following Cesarean sections (CS) to determine the characteristics associated with two etiologies: (1) prolonged obstructed labor; and (2) a complication of CS following obstructed labor. Methods We performed a cross-sectional study on abstracted data from all patients with urogenital fistula following CS who received care during a surgical campaign in a remote area of the Democratic Republic of the Congo (DRC). Descriptive analyses characterized patients with fistula related to obstructed labor versus CS. Univariate and multivariate logistic regression models identified factors associated with obstetric fistula after cesarean delivery following obstructed labor. Variables were included in the logistic regression models based upon biological plausibility. Results Among 125 patients, urogenital fistula etiology was attributed to obstructed labor in 77 (62%) and complications following CS in 48 (38%). Women with a fistula, attributed to obstructed labor, developed the fistula at a younger age (p = .04) and had a lower parity (p = .02). Attempted delivery before arriving at the hospital was associated with an increased risk of obstetric fistula after cesarean delivery following obstructed labor (p < .01). Conclusion CS are commonly performed on women who arrive at the hospital following prolonged obstructed labor and fetal demise, and account for almost 40% of urogenital fistula. Obstetric providers should assess maternal status upon arrival to prevent unnecessary CS and identify women at risk of developing a fistula.